Quality of life of elderly. Comparison between urban and rural areas - Darlene Mara dos Santos Tavares; Alisson Fernandes Bolina; Flavia Aparecida Dias; Pollyana Cristina dos Santos Ferreira; Vanderlei José Haas (Universidad de Antioquia, 2014)
Objective. Comparing the scores of quality of life according to place of residence (urban and rural areas). Methods. A cross-sectional study involving 2142 elderly in urban area and other 850 in rural area of the municipality of Uberaba (Minas Gerais, Brazil). Instruments used: Olders Americans Resources and Services, World Health Organization Quality of Life - BREF (WHOQOL-BREF) and World Health Organization Quality of Life Assessment for Older Adults (WHOQOL-OLD). Results. We found that in urban area predominated women and men in rural areas. It was common in two areas: 60Ⱶ70 years old, married marital status, schooling of 4 to 8 years of study and the income of a minimum wage. The elderly residing in the urban area with their children and in rural areas did so with the spouse. In the evaluation of the quality of life, rural elders presented scores significantly higher than the urban area in the domains of physical, psychological, and social relations in the WHOQOL-BREF; and in the facets of autonomy, past, present and future activities, social participation and intimacy of the WHOQOL-OLD. For the latter instrument facets sensory ability and of death and dying the elderly's urban area had higher scores than the rural area. Conclusion. The elders of the urban area showed a greater involvement of the quality of life than the residents in the rural area. Nurses who work in primary care should address health strategies according to the specific needs of the urban and rural areas.